SAT0367 Can We Differentiate Takayasu Arteritis from Atherosclerosis Using Carotid and Femoral Artery Doppler USG?. (15th July 2016) - Ugurlu, S.; Cetinkaya, F.; Keskin, F.E.; Melikoglu, M.; Hamuryudan, V.; Fresko, I.; Kadioglu, P.; Yurdakul, S.; Seyahi, E.
Abstract : Background: Clinicians can have difficulty in making differential diagnosis between Takayasu arteritis (TA) and atherosclerosis. This is especially true when laboratory evaluations and FDG PET are inconclusive. In addition to that atherosclerosis load is potentially increased in TA (1–2). About 1/3rd of the patients with TA had carotid artery plaques and almost half had diffuse aortic wall calcifications (1–2). Objectives: We thought that TA might have unique vascular changes distinct from atherosclerosis when evaluated with Doppler ultrasonography (USG). Methods: Consecutive patients with TA seen in the department of Rheumatology at Cerrahpasa Medical Faculty at Istanbul were studied along with healthy controls. TA patients and healthy controls were aged between 18 and 50 years. Patients with diabetes mellitus (DM) who were followed by the endocrinology outpatient clinic were also studied. For the purposes of this study, no age limit was set for patients with DM. Only females were studied. Traditional atherosclerotic risk factors were also assessed. The radiologist scanned the right and left common, internal and external carotids, carotid bulb as well as the right and left common femoral arteries using Doppler USG. Intima-media thickness (IMT) was measured and resistivity index was calculated. The presence of atherosclerotic plaques and diffuse IMT was assessed. Diffuse IMT was defined as diffuse homogenous intima-media thickening of at least 0.9 mm. Results: We studied 58 patients with TA (mean age: 43 ±11), 42 patients with DM (mean age: 57 ± 9) and 24 healthy controls (mean age: 41 ± 4). Patients with DM were significantly older and had significantly more atherosclerotic risk factors. The mean carotid IMT was comparable between TA and DM, whereas the mean femoral IMT was significantly lower in TA. The frequency of atherosclerotic plaques in both carotid and femoral arteries was significantly higher among patients with DM (Table). Presence of diffuse wall thickenning of at least 0.9 mm and turbulence were observed almost only among patients with TA. Finally the mean resistivity index was only significantly increased in TA (Table). Conclusions: Diffuse homogenous increase in IMT, presence of turbulence and higher resistivity index can be considered as suggestive of TA rather than atherosclerosis. This study showed that carotid and femoral artery USG may be helpful in differentiating TA from atherosclerosis. References: Seyahi E, et al. Ann Rheum Dis. 2006. Seyahi E, et al. Semin Arthritis Rheum. 2013. Disclosure of Interest: None declared